WASIAT WAJIBAH PADA FURU’ WARIS - Ritonga, Raja (IAIN Tulungagung, 2021)
Wasiat wajibah is an ijtihad’s concept about someone’s wealth changing to another who has no right to get the inheritance. However, together with the appearance of conception and implementation, so there is the contradiction of the application and realization. This research is library research and designed descriptive qualitative. The result of the research describes that wasiat wajibah is given to furu’ heir (generation) from inherit. As for the calculation concept of wasiat wajibah, a child who passed away is reputed alive and becomes heir. By the boy’s line, wasiat wajibah is given only to the grandchild and great grandchild’s level. While from the woman’s line, wasiat wajibah is only by the grandchild’s level. The implementation of wasiat wajibah is done if a grandfather is never given a gift to his passed away children when they are alive. The digit of 1/3 becomes the maximum limit which will accept by grandchild and great-grandchild. So, if the acceptance digit by children is more than 1/3, then their generation only gets 1/3 and the rest is given to another heir.